Quantitative phase imaging for medical diagnosis. Issue 2 (19th August 2016) - Majeed, Hassaan; Sridharan, Shamira; Mir, Mustafa; Ma, Lihong; Min, Eunjung; Jung, Woonggyu; Popescu, Gabriel
Abstract : Optical microscopy is an indispensable diagnostic tool in modern healthcare. As a prime example, pathologists rely exclusively on light microscopy to investigate tissue morphology in order to make a diagnosis. While advances in light microscopy and contrast markers allow pathologists to visualize cells and tissues in unprecedented detail, the interpretation of these images remains largely subjective, leading to inter‐ and intra‐observer discrepancy. Furthermore, conventional microscopy images capture qualitative information which makes it difficult to automate the process, reducing the throughput achievable in the diagnostic workflow. Quantitative Phase Imaging (QPI) techniques have been advanced in recent years to address these two challenges. By quantifying physical parameters of cells and tissues, these systems remove subjectivity from the disease diagnosis process and allow for easier automation to increase throughput. In addition to providing quantitative information, QPI systems are also label‐free and can be easily assimilated into the current diagnostic workflow in the clinic. In this paper we review the advances made in disease diagnosis by QPI techniques. We focus on the areas of hematological diagnosis and cancer pathology, which are the areas where most significant advances have been made to date. [Image adapted from Y. Park, M. Diez‐Silva, G. Popescu, G. Lykotrafitis, W. Choi, M. S. Feld, and S. Suresh, Proc. Natl. Acad. Sci. 105, 13730–13735 (2008).] Abstract : With the development of more sophisticated optical instruments and greater computing power, disease diagnosis methods are likely to become more quantitative, accurate and objective. In this article, we review the application of Quantitative Phase Imaging (QPI), a label‐free quantitative light microscopy technique, as a tool for clinical diagnosis. By discussing various approaches that target different diseases, we show that QPI provides novel information on disease biology and progression, thus becoming an important addition to the diagnostic toolbox for clinicians.